What Is the Value of Wild Bee Pollination for Wild Blueberries and Cranberries, and Who Values It? - Aaron K. Hoshide (Environments, 2018)
Pollinator conservation efforts and growing interest in wild bee pollination have increased markedly in the last decade, making it increasingly important to have clear and practical estimates of the value of pollinators to agriculture. We used agricultural statistics, socio-economic producer surveys, and agronomic field research data to estimate traditional pollination value metrics and create novel approaches to the valuation of the ecosystem services provided by wild pollinators. Using two regionally important United States (USA) crops—Maine wild blueberry and Massachusetts cranberry—as models, we present the perceived values of wild bee pollinators from the perspectives of both consumers and producers. The net income attributable to wild bees was similar for wild blueberry ($613/ha) and cranberry ($689/ha). Marginal profit from incrementally adding more hives per ha was greater from stocking a third/fourth hive for cranberry ($6206/ha) than stocking a ninth/10th hive for wild blueberry ($556/ha), given the greater initial responsiveness of yield, revenue, and profit using rented honey bee hives in cranberry compared with wild blueberry. Both crops’ producers were willing to annually invest only $140–188/ha in wild pollination enhancements on their farms, justifying government financial support. Consumers are willing to pay ≈6.7 times more to support wild bees than producers, which indicates a potential source for market-based subsidies for invertebrate conservation.